Modulating effect of SIRT1 activation induced by resveratrol on Foxo1‐associated apoptotic signalling in senescent heart. (14th April 2014) - Sin, Thomas K.; Yu, Angus P.; Yung, Benjamin Y.; Yip, Shea Ping; Chan, Lawrence W.; Wong, Cesar S.; Ying, Michael; Rudd, John A.; Siu, Parco M.
Abstract : Key points: Cardiac function is impaired and Foxo1/Bim‐related apoptotic signalling is up‐regulated in senescent heart Activation of SIRT1 deacetylase activity by resveratrol attenuates the Foxo1/Bim signalling axis in senescent heart Abstract: Elevations of cardiomyocyte apoptosis and fibrotic deposition are major characteristics of the ageing heart. Resveratrol, a polyphenol in grapes and red wine, is known to improve insulin resistance and increase mitochondrial biogenesis through the SIRT1–PGC‐1α signalling axis. Recent studies attempted to relate SIRT1 activation by resveratrol to the regulation of apoptosis in various disease models of cardiac muscle. In the present study, we tested the hypothesis that long‐term (8‐month) treatment of resveratrol would activate SIRT1 and improve the cardiac function of senescent mice through suppression of Foxo1‐associated pro‐apoptotic signalling. Our echocardiographic measurements indicated that the cardiac systolic function measured as fractional shortening and ejection fraction was significantly reduced in aged mice when compared with the young mice. These reductions, however, were not observed in resveratrol‐treated hearts. Ageing significantly reduced the deacetylase activity, but not the protein abundance of SIRT1 in the heart. This reduction was accompanied by increased acetylation of the Foxo1 transcription factor and transactivation of its target, pro‐apoptotic Bim. Subsequent analyses indicated that pro‐apoptotic signalling measured as p53, Bax and apoptotic DNA fragmentation was up‐regulated in the heart of aged mice. In contrast, resveratrol restored SIRT1 activity and suppressed elevations of Foxo1 acetylation, Bim and pro‐apoptotic signalling in the aged heart. In parallel, resveratrol also attenuated the ageing‐induced elevations of fibrotic collagen deposition and markers of oxidative damage including 4HNE and nitrotyrosine. In conclusion, these novel data demonstrate that resveratrol mitigates pro‐apoptotic signalling in senescent heart through a deacetylation mechanism of SIRT1 that represses the Foxo1–Bim‐associated pro‐apoptotic signalling axis.